Vitamin D analogues: Potential use in cancer treatment. (April 2017) - Duffy, Michael J.; Murray, Alyson; Synnott, Naoise C.; O'Donovan, Norma; Crown, John
Highlights: Some epidemiological studies suggest that low levels of vitamin D are associated with an increased risk of developing specific cancers. Vitamin D (calcitriol) as well as several of its synthetic analogues have been shown to inhibit tumor growth in preclinical models. Some vitamin D analogues with low calcemic inducing activity have progressed to clinical trials in patients with cancer. Preliminary results suggest that these vitamin D analogs have minimal toxicity, but clear evidence of efficacy remains to be shown. Abstract: The vitamin D receptor (VDR) is a member of the thyroid-steroid family of nuclear transcription factors. Following binding of the active form of vitamin D, i.e., 1, 25(OH)2 D3 (also known as calcitriol) and interaction with co-activators and co-repressors, VDR regulates the expression of several different genes. Although relatively little work has been carried out on VDR in human cancers, several epidemiological studies suggest that low circulating levels of vitamin D are associated with both an increased risk of developing specific cancer types and poor outcome in patients with specific diagnosed cancers. These associations apply especially in colorectal and breast cancer. Consistent with these findings, calcitriol as well as several of its synthetic analogues have been shown to inhibit tumor cell growth in vitro and in diverse animal model systems. Indeed, some of these vitamin D analogues with low calcemic inducing activity (e.g., EB1089, inecalcitol, paricalcitol) have progressed to clinical trials in patients with cancer. Preliminary results from these trials suggest that these vitamin D analogues have minimal toxicity, but clear evidence of efficacy remains to be shown. Although evidence of efficacy for mono-treatment with vitamin D analogues is currently lacking, several studies have reported that supplementation with calcitriol or the presence of high endogenous circulating levels of vitamin D enhances response to standard therapies.